1993
DOI: 10.1254/jjp.63.479
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-Sensitive Sensory Nerves in Recovery of Gastric Mucosal Integrity after Damage by Sodium Taurocholate in Rats

Abstract: ABSTRACT-We compared the recovery process of gastric mucosal integrity after damage by 20 mM sodium taurocholate (TC) in control, sensory deafferented and indomethacin-treated rats. Under anesthe tized conditions, the stomach was mounted on a chamber and perfused with saline or 50 mM HCI. Applica tion of TC (30 min) to the saline-perfused stomach produced a marked reduction in the potential difference (PD) (surface epithelial damage), followed by increases of gastric mucosal blood flow (GMBF) and luminal pH (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 22 publications
5
37
0
Order By: Relevance
“…Although gastric hyperemia is not the exclusive mechanism of gastric cytoprotection as induced by PGE 2 or capsaicin-sensitive afferent neurons (Stroff et al, 1996;Araki et al, 2000), GMBF is considered to be a factor in capsaicin-induced gastric protection under certain experimental conditions (Holzer et al, 1991;Takeuchi et al, 1993). We previously reported that the gastric hyperemic response to capsaicin was also significantly mitigated by indomethacin, suggesting an involvement of endogenous PGs in this action (Matsumoto et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gastric hyperemia is not the exclusive mechanism of gastric cytoprotection as induced by PGE 2 or capsaicin-sensitive afferent neurons (Stroff et al, 1996;Araki et al, 2000), GMBF is considered to be a factor in capsaicin-induced gastric protection under certain experimental conditions (Holzer et al, 1991;Takeuchi et al, 1993). We previously reported that the gastric hyperemic response to capsaicin was also significantly mitigated by indomethacin, suggesting an involvement of endogenous PGs in this action (Matsumoto et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including our own, have shown that the protective effect of capsaicin is mitigated by prior administration of indomethacin, suggesting an involvement of endogenous PGs in this action (Takeuchi et al, 1991b(Takeuchi et al, , 1993Uchida et al, 1991;Brzozowski et al, 1993). It is known that endogenous PGs sensitize the sensory neurons to nociceptive stimulation (Ohishi et al, 1999;Ueno et al, 2000).…”
mentioning
confidence: 86%
“…It is known that the stomach responds to mucosal-damaging agents by altering various functions such as mucosal blood flow (Nobuhara and Takeuchi, 1984;Takeuchi et al, 1986Takeuchi et al, , 1993. Although the role of PGs may vary with different types of mucosal irritants used to break the gastric mucosal barrier in the presence of luminal acid, this process is essentially mediated by endogenous PGs when the barrier is disrupted by TC (Nobuhara and Takeuchi, 1984;Takeuchi et al, 1986;Hirata et al, 1997).…”
Section: Cox Isozymes and Gastric Barrier Disruption 717mentioning
confidence: 99%
“…It is known that the application of mild irritants to the stomach causes an increase in gastric mucosal blood flow (GMBF) as well as a decrease in acid secretion (Whittle, 1983;Takeuchi et al, 1986Takeuchi et al, , 1993. These agents damage the surface epithelium of the gastric mucosa, resulting in acid back-diffusion, yet they rarely cause macroscopically visible damage and actually protect the stomach against necrotizing agents (Holzer et al, 1991;Takeuchi et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation